Semantic Versus Orthographic Preferences in Aphasia: Behavioral Evidence. Issue 3 (June 2022) - DeMetropolis, Susan M.; Goldfarb, Robert
In this study, we compared the orthographic and semantic preferences of healthy adults and age and gender matched adults with aphasia, an acquired language disorder. Previous research in word retrieval and word associations has addressed semantic and phonological connections, but it has not as often included analyses of orthographic skills. We matched (on age and gender) 10 neurotypical adults and 11 older adults with aphasia and administered to both groups a lexical discrimination task requiring them to select, from 18 choices, those words that were most different from three words (daughter, laughter, son). Among the choices were foil words (e.g., daughter), orthographic similarities (laughter) and semantic similarities (son). Results revealed that individuals with aphasia focused on orthographic differences, while healthy adults chose semantic differences. Further studies should further explore this orthographic focus to develop treatment strategies, using behavioral and objective measures, for word-finding deficits in aphasia.